﻿Pharmacy graduates differences between governmental and private universities in Jordan - Saif Aldeen Jaber (Pensoft Publishers, 2022)
Jordan is an attractive country for Jordanian and non-Jordanian university students in which it has two types of universities (private and governmental). Pharmacy is one of the fields to be studied by students due to the wide range of jobs involved in the healthcare and pharmaceutical sectors. Thus, a high need for good quality assurance and collaboration between universities is needed due to the high competition among pharmacy graduates to build on their strengths and overcome their weaknesses. Method: A cross-sectional standardized online survey was conducted for private and governmental universities in Jordan graduates using a 19-item questionnaire. Results: Of a total number of 3771 pharmacy graduates, 1755 students (46.5) % were from private universities and 2016 (53.5)% were from governmental universities working in different pharmaceutical and non-pharmaceutical fields participated in this study. According to SPSS results, the type of university has a strong and significant correlation with job field, graduates' nationality, satisfaction, and cost of study with a P-value of less than 0.001. Conclusion: pharmacy institutions at private universities have a different system when comparing it with governmental universities which have a major contribution to pharmacy graduates. Thus, a community of practice from different institutions should be made to improve graduate outcomes.